2016
DOI: 10.1021/acs.jpca.5b11021
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer between Anionic Corrole and DNA

Abstract: The interaction between a water-soluble anionic Ga(III) corrole [Ga(tpfc)(SO3Na)2] and calf thymus DNA (ct-DNA) has been investigated by using femtosecond transient absorption spectroscopy. A significant broadening from 570 to 585 nm of positive absorption band of the blend of Ga(tpfc)(SO3Na)2 and ct-DNA (Ga(tpfc)(SO3Na)2-ctDNA) has been observed from 0.15 to 0.50 ps after photoexcitation of Ga(tpfc)(SO3Na)2 into the Soret band. The control experiment has been performed on the model DNA ([poly(dG-dC)]2) rich i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 72 publications
(116 reference statements)
1
16
0
Order By: Relevance
“…Therefore, base electron abstraction by the WE mechanistically is comparable to a direct ionization via excitation across the HUMO-LUMO (lowest unoccupied molecular orbital) gap as indicated by the UV light absorbance around 260 nm (also known as X band) [ 68 ]. Fig 10 displays nucleobase and base-pair highest occupied molecular orbital (HOMO) energy levels estimated in [ 69 71 ] relative to vacuum electron energy (right axis) and on a Ag/AgCl potential scale (left axis). Given the assumptions, used in these calculations, as well as covalent and non-covalent interactions in a double helix, these values are to be treated as approximate, nevertheless the relative nucleic acid base oxidation potentials were experimentally confirmed [ 14 , 20 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, base electron abstraction by the WE mechanistically is comparable to a direct ionization via excitation across the HUMO-LUMO (lowest unoccupied molecular orbital) gap as indicated by the UV light absorbance around 260 nm (also known as X band) [ 68 ]. Fig 10 displays nucleobase and base-pair highest occupied molecular orbital (HOMO) energy levels estimated in [ 69 71 ] relative to vacuum electron energy (right axis) and on a Ag/AgCl potential scale (left axis). Given the assumptions, used in these calculations, as well as covalent and non-covalent interactions in a double helix, these values are to be treated as approximate, nevertheless the relative nucleic acid base oxidation potentials were experimentally confirmed [ 14 , 20 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Femtosecond transient absorption spectra were recorded with 400 nm excitation, using a pump−probe apparatus described previously. 29 Nanosecond transient absorption measurements were performed on another pump−probe setup previously reported, after excitation at 532 nm. 28 The triplet absorption decay curves were well fitted with a single-exponential function convoluted with a Gaussian response function.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It was shown that an ultrafast electron transfer ET between (SO 3 Na) 2 TPFCorrGa and the guanine bases of ct-DNA occurred within the pulse duration equal to 156 fs. 273 Cobalt(III) mono-hydroxyl and phenothiazine corrole complexes were prepared and studied (Fig. 97).…”
Section: Photodynamic Therapy (Pdt) Applicationsmentioning
confidence: 99%
“…96 Structures of the halogenated gallium corroles 272 and the anionic disulfonic corrole gallium corrole. 273 Fig. 97 Free-base and cobalt corroles with -OH or phenothiazine group.…”
Section: Photodynamic Therapy (Pdt) Applicationsmentioning
confidence: 99%